Effect on Flexural Strength in Concrete Modified with Recycled Concrete - Ospina Lozano, Sandra Elodia (2025)
The current need for alternatives to reduce the environmental impact by increasing quarrying and use the resulting materials demolition processes, this paper the results are presented in different replacing traditional types of concrete on them, added resulting from the process of recycling concrete. To develop this work the water / cement ratios were varied and steel fibers are added in different percentages, leading to obtain direct effects on physical and mechanical properties of concrete studied; as a result of the investigation it was found that a design can be made of traditional concrete mixture a decrease in resistance factor ranging from 50% to 75 % of the expected resistance, for this test standard ASTM was used C39- ASTM C78 (NTC 6731 and INV e -414 to 073).